2006
DOI: 10.1289/ehp.8174
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gene Expression Profiles in Immortalized Human Urothelial Cells Exposed to Inorganic Arsenite and Its Methylated Trivalent Metabolites

Abstract: Inorganic arsenic is an environmental carcinogen. The generation of toxic trivalent methylated metabolites complicates the study of arsenic-mediated carcinogenesis. This study systematically evaluated the effect of chronic treatment with sodium arsenite (iAsIII), monomethylarsonous acid (MMAIII), and dimethylarsinous acid (DMAIII) on immortalized human uroepithelial cells (SV-HUC-1 cells) using cDNA microarray. After exposure for 25 passages to iAsIII (0.5 μM), MMAIII (0.05, 0.1, or 0.2 μM), or DMAIII (0.2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 80 publications
3
20
0
Order By: Relevance
“…The role of other factors such as tissue-specific variation, different dosages, and exposure times in the regulation of oxidative stressresponsive genes can not be rule out. A result similar to ours of (no major change in the oxidative stress-related genes from longterm arsenic-treated cells) was reported by microarray analysis (Su et al, 2006). Our present study together with the earlier report of no major changes in oxidative stress-responsive genes from long-term arsenic-treated cells suggest that oxidative stress-related genes may be involved in the carcinogenic process at a time point earlier than the one used in our study.…”
Section: Figsupporting
confidence: 92%
See 1 more Smart Citation
“…The role of other factors such as tissue-specific variation, different dosages, and exposure times in the regulation of oxidative stressresponsive genes can not be rule out. A result similar to ours of (no major change in the oxidative stress-related genes from longterm arsenic-treated cells) was reported by microarray analysis (Su et al, 2006). Our present study together with the earlier report of no major changes in oxidative stress-responsive genes from long-term arsenic-treated cells suggest that oxidative stress-related genes may be involved in the carcinogenic process at a time point earlier than the one used in our study.…”
Section: Figsupporting
confidence: 92%
“…All genes had decreased expression with higher (100 ng/ml and 1 μg/ml) concentrations of arsenic, suggesting that arsenic affects the cell mostly through inhibition of gene expression. Similar pattern of downregulation of genes as a choice of arsenic for its effect than upregulation of genes was recently reported using microarray analysis (Su et al, 2006).…”
Section: Figsupporting
confidence: 75%
“…We have previously observed that the expression of intracellular IL1R2 is enhanced in long term arsenic-exposed human urothelial cells (28). Furthermore, we showed that the ectopic expression of IL1R2 activates intracellular IL-1␣ signaling and increases the transcription of IL-6, IL-8, and collagen and the migration of human urothelial cells (17).…”
mentioning
confidence: 65%
“…First, arsenic carcinogenesis is cell-type specific, so the use of only transitional cells avoids potentially misleading information from other types of cells in the bladder. Secondly, urothelial cell lines, such as HUC-1 and UROtsa, may have inactivated p53 protein because of transformation with SV40 large T antigen [Rossi et al, 2001;Su et al, 2006]. Studies showed that cells without functional p53 proteins were more sensitive to arsenic and have different cellular responses than cells with functional p53 [Kircelli et al, 2007].…”
Section: Discussionmentioning
confidence: 99%